CBS mutations are good predictors for B6‐responsiveness: A study based on the analysis of 35 Brazilian Classical Homocystinuria patients. Issue 2 (20th January 2018) - Poloni, Soraia; Sperb‐Ludwig, Fernanda; Borsatto, Taciane; Weber Hoss, Giovana; Doriqui, Maria Juliana R.; Embiruçu, Emília K.; Boa‐Sorte, Ney; Marques, Charles; Kim, Chong A.; Fischinger Moura de Souza, Carolina; Rocha, Helio; Ribeiro, Marcia; et al.
Abstract: Background: Classical homocystinuria (HCU) is a monogenic disease caused by the deficient activity of cystathionine β‐synthase (CβS). The objective of this study was to identify the CBS mutations in Brazilian patients with HCU. Methods: gDNA samples were obtained for 35 patients (30 families) with biochemically confirmed diagnosis of HCU. All exons and exon‐intron boundaries of CBS gene were sequenced. Gene expression analysis by qRT‐PCR was performed in six patients. Novel missense point mutations were expressed in E. coli by site‐directed mutagenesis. Results: Parental consanguinity was reported in 16 families, and pyridoxine responsiveness in five (15%) patients. Among individuals from the same family, all presented the same phenotype. Both pathogenic mutations were identified in 29/30 patients. Twenty‐one different mutations were detected in nine exons and three introns; being six common mutations. Most prevalent were p.Ile278Thr (18.2%), p.Trp323Ter (11.3%), p.Thr191Met (11.3%), and c.828+1G>A (11.3%). Eight novel mutations were found [c.2T>C, c.209+1delG, c.284T>C, c.329A>T, c.444delG, c.864_868delGAG c.989_991delAGG, and c.1223+5G>T]. Enzyme activity in E. coli‐ expressed mutations was 1.5% for c.329A>T and 17.5% for c.284T>C. qRT‐PCR analysis revealed reduced gene expression in all evaluated genotypes: [c.209+1delG; c.572C>T]; [c.2T>C; c.828+1G>A]; [c.828+1G>A; c.1126G>A]; [c.833T>C; c.989_991delAGG]; [c.1058C>T; c.146C>T]; and [c.444delG; c.444delG]. The expected phenotype according to the genotype (pyridoxine responsiveness) matched in all cases. Conclusions: Most patients studied were pyridoxine nonresponsive and presented early manifestations, suggesting severe phenotypes. Many private mutations were observed, but the four most prevalent mutations together accounted for over 50% of mutated alleles. A good genotype–phenotype relationship was observed within families and for the four most common mutations. Abstract : Here, we describe CβS mutations in 35 Brazilian patients with classical homocystinuria. Twenty‐one different mutations were detected. The most prevalent were p.Ile278Thr (18.2%), p.Trp323Ter (11.3%), p.Thr191Met (11.3%), and c.828+1G>A (11.3%). Eight novel mutations were found. Most patients studied were pyridoxine nonresponsive and presented early manifestations, suggesting severe phenotypes. A good genotype–phenotype relationship was observed within families and for common mutations.